Fast Slant-Hadamard Transform Algorithm - Hakobyan, Sonik R. (Mathematical Problems of Computer Science, 2021)
In this paper, we investigate an efficient algorithm for computation of parametric Slant-Hadamard transforms. We present the Slant-Hadamard matrix of order n 2 as a product of sparse matrices, develop the appropriate fast Slant-Hadamard transform and its complexity. In the end we present the detailed example of factoring of SlantHadamard transform matrix of order 8 and Matlab code for implementation SlantHadamard transform.